2021
DOI: 10.1016/j.phro.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Professional practice changes in radiotherapy physics during the COVID-19 pandemic

Abstract: Background and purpose The COVID-19 pandemic has imposed changes in radiotherapy (RT) departments worldwide. Medical physicists (MPs) are key healthcare professionals in maintaining safe and effective RT. This study reports on MPs experience during the first pandemic peak and explores the consequences on their work. Methods A 39-question survey on changes in departmental and clinical practice and on the impact for the future was sent to the global MP community. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…21,61,62 Early reports indicate that radiation oncologists from LMICs have increased their utilization of hypofractionated regimens since the beginning of the COVID-19 pandemic with one report from India finding that 9% of radiation oncologists had implemented hypofractionated treatments for the first time. [63][64][65][66] Similarly, multiple institutions have reported that patients on average are being treated with fewer fractions per treatment course since the beginning of the COVID-19 pandemic, suggesting increased adoption of hypofractionated treatment regimens. 67,68 Despite these recent advances in the adoption of hypofractionated radiotherapy regimens, the results of the ESTRO-GIRO survey indicate that the regions that would most benefit from the widespread adoption of hypofractionated treatments also have the lowest utilization rates.…”
Section: State Of Hypofractionation In Lmicsmentioning
confidence: 99%
“…21,61,62 Early reports indicate that radiation oncologists from LMICs have increased their utilization of hypofractionated regimens since the beginning of the COVID-19 pandemic with one report from India finding that 9% of radiation oncologists had implemented hypofractionated treatments for the first time. [63][64][65][66] Similarly, multiple institutions have reported that patients on average are being treated with fewer fractions per treatment course since the beginning of the COVID-19 pandemic, suggesting increased adoption of hypofractionated treatment regimens. 67,68 Despite these recent advances in the adoption of hypofractionated radiotherapy regimens, the results of the ESTRO-GIRO survey indicate that the regions that would most benefit from the widespread adoption of hypofractionated treatments also have the lowest utilization rates.…”
Section: State Of Hypofractionation In Lmicsmentioning
confidence: 99%
“… 21 Recent evidence indicates that working remotely was introduced for medical physicists, dosimetrists and the wider medical team. 22 , 23 Evidence also suggests that access to remote working is not universally available and is limited in low- and middle-income countries (LMICs) and developing countries. 24 , 25 In many industries, hybrid working or a full time “return to the office” policies have been introduced.…”
Section: Alterations In Working Patternsmentioning
confidence: 99%
“…Starting these discussions should be a low-threshold action for all team members. As such, different perspectives between groups with different leadership levels, as observed by Bertholet et al [43], can be combined to focus on constructive solutions where they are needed. This communication should be organised through team reflection, making it a collective responsibility to find solutions that adequately address individual needs.…”
Section: Mental Healthmentioning
confidence: 99%